KINSHIP OF DOUBLE HARMONIC MAJOR SCALE AND RAGA BHAIRAV OF INDIAN MUSIC - Chauhan, Mukul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research paper shares the kinship between Indian Raga and Western music scale. Western system of music consists of scales and chords. A scale is of ascending and descending order of notes. The term scale comes from the Latin word scala meaning ladder. A scale is considered a set of intervals. An interval is a number of semi tones that separates from one pitch to a different pitch. A semitone, also called a half step or a half tone, is always termed the smallest musical interval considered in Western music. It is defined the interval between two adjacent notes of a 12-tone scale from C to C#. Two semi tones are termed as a whole tone or whole step. A specific scale is defined by its interval patterns and by a special note also called as the root note of the scale or the tonic note. For example-in a C-major scale C is the tonic note. There are seven basic degrees in western music which can also be known as seven swaras in Indian music. For example: Degrees in relation with Key C in Western music: 1 2 3 4 5 6 7 8 Sa Re Ga Ma Pa Dha Ni Sa In Indian music twelve semi tones can be defined as seven pure notes or shudh swaras and five altered notes known as vikrit swaras. Out of seven notes Sa and Pa are constant notes which do not change their positions and Re Ga Dha and Ni can be played pure as well as flat, also known as Komal swaras. Ma note can be played as a pure note or Tivra swara also known as a sharp note.